DOI: 10.4995/thesis/10251/8380
|View full text |Cite
|
Sign up to set email alerts
|

Estudio de la absorción y translocación del nitrógeno en cítricos en función del aporte estacional del abono nitrogenado mediante el uso de la técnica de dilución isotópica

Abstract: Dª Belén Martínez Alcántara, Ingeniera Agrónoma, ha realizado bajo nuestra dirección el trabajo que, con el título "Estudio de la absorción y translocación del nitrógeno en cítricos en función del aporte estacional del abono nitrogenado, mediante la técnica de dilución isotópica", presenta para optar al grado de Doctora Ingeniera Agrónoma.Para que así conste a los efectos oportunos, firman el presente documento en Moncada a 9 de marzo de 2010. Fdo. D. Francisco Legaz Paredes Fdo. Dª Ana Quiñones OliverA mis pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 65 publications
(137 reference statements)
1
1
0
Order By: Relevance
“…Changes produced in the distribution of soil moisture did not enhance the total production of lemon trees in 3L. A similar response has been observed in citrus such as mandarin [57] and lemon [18], where the harvesting of the crop was carried out in a single harvest, as well as in other crops, such as olive and apple, when full irrigation with 100% of the crop's needs were applied [61,62] with different numbers of drippers per tree, but the same irrigation dose in surface drip irrigation. Nevertheless, in hazelnut trees irrigated with different percentages of wet soil volume, trees yielded more as the percentages of wet soil volume were increased [63].…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…Changes produced in the distribution of soil moisture did not enhance the total production of lemon trees in 3L. A similar response has been observed in citrus such as mandarin [57] and lemon [18], where the harvesting of the crop was carried out in a single harvest, as well as in other crops, such as olive and apple, when full irrigation with 100% of the crop's needs were applied [61,62] with different numbers of drippers per tree, but the same irrigation dose in surface drip irrigation. Nevertheless, in hazelnut trees irrigated with different percentages of wet soil volume, trees yielded more as the percentages of wet soil volume were increased [63].…”
Section: Discussionsupporting
confidence: 78%
“…The higher leaf N and Fe concentrations found in 3L trees suggest that a more horizontal fertiliser distribution, as well as lower irrigation lengths of the events, can reduce possible losses of nitrates due to percolation, enhancing the efficiency of N and Fe application in lemon trees. Therefore, this could contribute to a longer presence of the fertiliser in the soil area for effective root uptake, especially during the season when N application is greater (mainly during phase II of fruit growth) [57], contributing to more sustainable fertilisation. In fact, [58] indicated that the uniformity of fertiliser application depends on that of the irrigation system application, in our case being better in the 3L irrigation system.…”
Section: Discussionmentioning
confidence: 99%